The relationship between intraocular pressure and random blood glucose levels with open angle glaucoma - Srivastava, Namrata; Yadav, Y. S.; Kumar, Prashant (International Journal Of Community Medicine And Public Health, 2023)
Background: Primary open-angle glaucoma (POAG) is a multifactorial chronic optic neuropathy, characterized by progressive loss of retinal ganglion cells (RGC), leading to structural damage to the optic nerve head (ONH), retinal nerve fibre layer (RNFL), with visual field defects. This study was carried out at the department of optometry GSVM Medical College, Kanpur, UP from December 2015 to September 2017. Objectives were determination of the relationship between intraocular pressure and blood glucose levels in patients with primary open-angle glaucoma. Methods: A total of 74 subjects, 28 males and 46 females were used for the study. The Accu-Chek glucometer was used to measure the random blood glucose level and the intraocular pressure was measured using the Perkins applanation tonometer. Results: The mean intraocular pressure was 16.57±3.97 while the mean random blood glucose level was 168.43±108.48. Analysis of the SPSS version 23 data using the Pearson product-moment correlation coefficient at a significance level of 0.05 and a 95% confidence interval revealed no correlation between IOP and random blood glucose (p and gt; 0.05). People with primary open-angle glaucoma are advised to have their blood sugar levels monitored frequently. Conclusions: This study showed that there was no significant correlation between intraocular pressure and random blood glucose levels in patients with primary open-angle glaucoma. This would suggest that diabetics should be monitored regularly for intraocular pressure to detect an early onset of glaucoma.